2008
DOI: 10.2223/jped.1795
|View full text |Cite
|
Sign up to set email alerts
|

Community violence and alcohol abuse among adolescents: a sex comparison

Abstract: ResumoObjetivo: Verificar a existência de associação entre vitimização e uso de álcool entre meninos e meninas de Porto Alegre (RS).Métodos: Foi realizado um estudo transversal. Participaram estudantes de escolas públicas com idade entre 10 e 19 anos, da 5ª série do ensino fundamental até a 3ª série do ensino médio, compondo amostra por conglomerados em dois estágios, definidas pelas características socioeconômicas do bairro da escola e pela turma. A coleta de dados foi realizada por questionário padronizado d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
18
0
11

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 26 publications
8
18
0
11
Order By: Relevance
“…It is known that addictive behavior among adults usually has its roots in abuse of both alcohol and tobacco during adolescence [9,18,20,21,24,41]. Additionally, smoking and drinking seem to increase the odds of the development of abuse of other substances, regardless of gender or age [17,27,29,38,40,49,61,62]. In our study, we observed a higher frequency and intensity of alcohol use among smokers, which corresponds well with previously published results.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…It is known that addictive behavior among adults usually has its roots in abuse of both alcohol and tobacco during adolescence [9,18,20,21,24,41]. Additionally, smoking and drinking seem to increase the odds of the development of abuse of other substances, regardless of gender or age [17,27,29,38,40,49,61,62]. In our study, we observed a higher frequency and intensity of alcohol use among smokers, which corresponds well with previously published results.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, two thirds of the Serbian adolescents reported a first drinking occasion before completing high school, while the other third had the same experience while attending elementary school. Despite these obvious inter-country variations in behavior, nearly all adolescents worldwide have already consumed alcohol by the time they reach 18 years of age [3,17,18,[24][25][26][27][28]. Furthermore, more than half of our study subjects reported being intoxicated at least once, supporting the results of previous surveys [3,10,16,29].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…A prevalência do uso de tabaco e bebidas alcoólicas em adolescentes de São Paulo foi maior do que os dados encontrados em outros estudos nacionais, como por exemplo, em jovens de Florianópolis (SC) 23 e Porto Alegre (RS) 24 . Portanto, programas de intervenção são necessários no sentido de estimular a prática de atividade física diária e, também, com o objetivo de diminuir o uso de tabaco e bebidas alcoólicas em adolescentes do ensino médio de São Paulo.…”
Section: Discussionunclassified
“…24 Therefore, intervention programs are necessary to stimulate the daily practice of physical activities, as well as to reduce smoking and alcohol intake among high school students from São Paulo.…”
Section: Discussionmentioning
confidence: 99%